Ethylene-based polymers and processes for producing them
Patent Information
- Application Number
- JP2026516019
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2024-08-22
- Publication Date
- 2026-10-14
Smart Images

Figure 2026534065000018 
Figure 2026534065000019 
Figure 2026534065000020
Abstract
Description
[Background technology]
[0001] The blow-fill-seal (BFS) process is a sterile processing technique used in medical packaging applications, such as the filling and packaging of sterile pharmaceutical preparations. Low-density polyethylene (LDPE) is known in the art for use in the BFS process due to its low levels of extractables and leaches. High levels of extractables and leaches are detrimental to medical applications requiring high-purity materials. However, LDPE cannot be sterilized at the higher temperatures required for some BFS applications.
[0002] Therefore, in this technical field, there is a recognized ongoing need for LDPE that is low in hexane extractables and can be sterilized at high temperatures for high-purity medical applications. Specifically, there is a need for LDPE with low hexane extractables that is suitable for medical applications, particularly for use in BFS processes. [Overview of the project]
[0003] This disclosure provides compositions. In one embodiment, a composition is provided which comprises an ethylene homopolymer. The ethylene homopolymer has (i) a density of 0.9285 g / cc to 0.9315 g / cc, (ii) a melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) a hexane extractable content of 0.2% to 0.7% by weight. This disclosure also provides articles formed from the compositions.
[0004] This disclosure provides articles. In one embodiment, articles are provided which comprise an ethylene homopolymer. The ethylene homopolymer has (i) a density of 0.9285 g / cc to 0.9315 g / cc, (ii) a melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) a hexane extractable content of 0.2% to 0.7% by weight.
[0005] definition All references to the periodic table refer to the version published by CRC Press, Inc., 1990–1991. References to element groups in this table are based on a new notation for numbering groups.
[0006] For the purposes of U.S. patent practice, the content of any referenced patent, patent application, or publication, in particular with respect to the disclosure of definitions (to the extent that it does not conflict with any definitions specifically provided in this disclosure), is incorporated by reference in its entirety (or its corresponding U.S. version is incorporated by reference in this way).
[0007] Numerical ranges disclosed herein include all values from the lower limit to the upper limit (including the lower and upper limits). In the case of ranges that include explicit values (e.g., 1 or 2, or 3 to 5, or 6 or 7), any subrange between any two explicit values is included (e.g., the above range of 1 to 7 includes subranges such as 1 to 2, 2 to 6, 5 to 7, 3 to 7, 5 to 6, etc.).
[0008] Unless otherwise stated, implied by the context, or customary in the art, all parts and percentages are based on weight, and all test methods are current as of the filing date of this disclosure.
[0009] As used herein, the terms “blend” or “polymer blend” refer to a mixture of two or more polymers. A blend may or may not be miscible (not phase-separated at the molecular level). A blend may or may not be phase-separated. A blend may or may not contain one or more domain configurations determined by transmission electron spectroscopy, light scattering, X-ray scattering, and other methods known in the art. A blend may be influenced by the physical mixing of two or more polymers at a macro level (e.g., melt blending or formulation of resins) or at a micro level (e.g., simultaneous formation in the same reactor).
[0010] The term "composition" refers to a mixture of the materials constituting the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0011] The terms "comprising", "including", "having" and their derivatives are not intended to exclude the presence of any additional component, step, or procedure, whether or not it is specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additive, adjuvant, or compound, whether polymeric or not, unless stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding recitation any other components, steps, or procedures, except those not essential to operability. The term "consisting of" excludes any component, step, or procedure not specifically delineated or listed. The term "or", unless stated otherwise, refers to the listed elements individually and in any combination.
[0012] An "ethylene-based polymer" is a polymer that contains more than 50 mole percent (mol%) of polymerized ethylene monomer (based on the total amount of polymerizable monomers), and may optionally contain at least one comonomer. Ethylene-based polymers include ethylene homopolymers, and ethylene copolymers (meaning units derived from ethylene and one or more comonomers). The terms "ethylene-based polymer" and "polyethylene" may be used interchangeably.
[0013] As used herein, the term "ethylene monomer" or "ethylene" refers to a chemical unit having two carbon atoms connected by a double bond, and each carbon is bonded to two hydrogen atoms, which is polymerized with other such chemical units.
[0014] As used herein, the term "linear low density polyethylene" (or "linear low density polyethylene, LLDPE") refers to units derived from ethylene and at least one C3 to C 10 α-olefin, or a linear ethylene / α-olefin copolymer containing a heterogeneous short chain branching distribution comprising units derived from a C4 to C8 α-olefin comonomer. LLDPE is characterized by little, if any, long chain branching, in contrast to conventional LDPE. LLDPE has a density of 0.910 g / cc to less than 0.940 g / cc.
[0015] The term "low density polyethylene" or "LDPE", also referred to as "high pressure ethylene polymer", is a highly long chain branched ethylene-based polymer that can be fully homopolymerized (ethylene homopolymer) or copolymerized (ethylene copolymer). LDPE resins typically have a density of 0.915 to 0.935 g / cm 3 It has a density within the range. LDPE is different from LLDPE.
[0016] "Olefin" is an unsaturated aliphatic hydrocarbon having a carbon-carbon double bond.
[0017] As used herein, the terms “polymer” or “polymer material” refer to compounds prepared by polymerizing monomers, whether of the same or different types, providing multiple and / or repeating “units” or “mer units” constituting the polymer in a polymeric form. For this reason, the general term “polymer” encompasses both the term “homopolymer,” commonly used to refer to polymers prepared from only one type of monomer, and the term “copolymer,” commonly used to refer to polymers prepared from at least two types of monomers. It also encompasses all forms of copolymers, such as random, block, etc. The terms “ethylene / α-olefin polymer” and “propylene / α-olefin polymer” refer to the above copolymers prepared by polymerizing ethylene or propylene with one or more additional polymerizable α-olefin monomers, respectively. Polymers are often referred to as "made of" one or more specific monomers, "based on" a specific monomer or type of monomer, or "containing" a specific monomer content. However, it should be noted that in this context, the term "monomer" is understood to refer to the polymerization residue of a specific monomer, and not to the non-polymerized species. In general, polymers as used herein are referred to as being based on a "unit," which is the polymerization form of the corresponding monomer.
[0018] Test method Density. Samples for density measurement were prepared according to ASTM D 4703-10. The samples were compressed at 374°F (190°C) for 5 minutes at 10,000 psi (68 MPa). The temperature was maintained at 374°F (190°C) for the above 5 minutes, and then the pressure was increased to 30,000 psi (207 MPa) for 3 minutes. This was followed by holding at 70°F (21°C) and 30,000 psi (207 MPa) for 1 minute. Density measurements were performed within 1 hour of sample compression using ASTM D792-08, Method B.
[0019] The melt index (MI or I2) was measured according to ASTM D 1238-10, conditions 190°C / 2.16 kg, Method B, and reported as grams of eluted per 10 minutes.
[0020] Triple Detector Gel Permeation Chromatography (TD-GPC). The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5), and a 4-capillary viscometer (DV) coupled to a Precision Detectors (now Agilent Technologies) Model 2040 2-angle laser light scattering (LS) detector. A 15-degree angle was used for all absolute light scattering measurements. The autosampler oven compartment was set to 160 degrees Celsius, and the column compartment to 150 degrees Celsius. The columns used were four Agilent "Mixed A" columns (30 cm, 20 microns, linear mixed-bed columns). The chromatography solvent used was 1,2,4-trichlorobenzene (TCB), containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was spurged with nitrogen. The injection volume used was 200 microliters, and the flow rate was 1.0 ml / min.
[0021] The GPC column set was calibrated using 21 polystyrene standards with narrow molecular weight distributions ranging from 580 to 8,400,000, placed in six "cocktail" mixtures with at least a 10-fold gap between individual molecular weights. The standards were purchased from Agilent Technologies. Polystyrene standards were prepared using 0.025 grams in 50 ml of solvent for molecular weights above 1,000,000, and 0.05 grams in 50 ml of solvent for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80°C with gentle stirring for 30 minutes, then cooled, and the room temperature solution was transferred to an autosampler dissolution oven at 160°C for 30 minutes and cooled. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)).
[0022] M ポリエチレン =A × (M ポリスチレン ) B (Equation 1) In the formula, M is the molecular weight, A has a value of 0.4074, and B is equal to 1.0.
[0023] A quintic polynomial was used to fit each polyethylene equivalent calibration point.
[0024] The total plate count of the GPC column set was performed using decane introduced into the blank sample via a micropump controlled by the PolymerChar GPC-IR system. The plate count of the chromatography system must be greater than 18,000 for four Agilent "Mixed A" columns (30 cm, 20 microns, linear mixed bed columns).
[0025] The sample was prepared semi-automatically using PolymerChar's "Instrument Control" software, with a target weight of 2 mg / mL. The solvent (containing 200 ppm BHT) was added to a vial with a pre-nitrogen-spurged septum cap via PolymerChar's high-temperature autosampler. The sample was dissolved at 160°C for 3 hours with "low-speed" shaking.
[0026] Mn (cc) , Mw (cc) , and Mz (cc) The calculation was based on GPC results using the PolymerChar GPCOne® software, obtained from the IR chromatogram with the baseline subtracted at each equally spaced data retrieval point (i), and the narrow standard calibration curve of point (i) from Equation 1, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph and following Equations 2 to 4.
[0027]
number
[0028] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. Using this flow rate marker (FM), the pump flow rate (nominal flow rate) of each sample was linearly corrected by RV-matching the respective RV of the decane peak in the sample (RV(FM sample)) with the RV of the decane peak during calibration in the narrow reference material (RV(FM calibrated)). At this time, it is assumed that any change in the time of the decane marker peak is related to a linear shift of the overall implemented flow rate (effective flow rate). After calibrating the system based on the peaks of the flow rate marker, the effective flow rate (relative to the narrow standard calibration) is calculated as shown in Equation 5. The processing of the flow rate marker peaks was performed via PolymerChar GPCOne™ software. An acceptable flow rate correction requires that the effective flow rate be within ±0.5% of the nominal flow rate. Effective Flow Rate = Nominal Flow Rate * × (RV(FM calibrated) / RV(FM sample)) (Equation 5)
[0029] Regarding the determination of viscometer and light scattering detector offsets from the IR5 detector, a systematic method for determining multi-detector offsets is performed in a manner consistent with that published by Balke, Mourey, et al. (Mourey and Balke, Chromatography Polym. Chpt 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym. Chpt 13, (1992)), using PolymerChar GPCOne™ software to optimize the triple detector log(MW and IV) results obtained from a linear homopolymer polyethylene reference material (3.5 > Mw / Mn > 2.2) with a molecular weight in the range of 115,000 to 125,000 g / mol to the results of the narrow standard column calibration obtained from the narrow reference material calibration curve.
[0030] Absolute molecular weight data was obtained using PolymerChar's GPCOne® software in a format consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injection concentration used in determining the molecular weight was obtained from the mass detector area and mass detector constant derived from one of the following: a suitable linear polyethylene homopolymer or a polyethylene standard material with a known weight-average molecular weight. The molecular weight calculated (using GPCOne®) was obtained using the light scattering constant derived from one or more of the polyethylene standards described below, and the refractive index concentration coefficient, dn / dc, of -0.104. In general, the mass detector response (IR5) and light scattering constant (determined using GPCOne®) should be determined from linear standards with a molecular weight greater than approximately 50,000 g / mol. Calibration of the viscometer (determined using GPCOne®) can be achieved using the method described by the manufacturer, or alternatively, by using published values of a suitable linear standard such as Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology, NIST). The specific viscosity area (DV) and injected mass for the calibration standard are used to calculate the viscometer constant (obtained using GPCOne®) related to its intrinsic viscosity. The chromatographic concentration is assumed to be low enough to eliminate the consideration of the second viral coefficient effect (concentration effect on molecular weight).
[0031] Absolute weight average molecular weight (MW) (Abs)) is obtained (using GPCOne®) from a light scattering (LS) area integrated chromatogram (factored by the light scattering constant) divided by the mass reconstructed from the mass constant and mass detector (IR5) area. The molecular weight and intrinsic viscosity response are linearly extrapolated (using GPCOne®) at the edge of the chromatogram where signal-to-noise is low. The other respective moments are Mn (abs) , Mw (abs) , and Mz (abs) This is calculated according to equations 6 to 8 below.
[0032]
number
[0033] The gpcBR branching index is determined by a triple-detector GPC (TD-GPC). The gpcBR branching index is determined by first calibrating the light scattering, viscosity, and infrared IR5 detectors, as described above. Then, a baseline is subtracted from the light scattering, viscometer, and IR5 (measurement channel) chromatograms. Next, an integration window is set to ensure that all low molecular weight retention volume ranges of the light scattering and viscometer chromatograms, which indicate the presence of detectable polymers from the infrared (IR5) chromatogram, are integrated. Then, the Mark-Houwink constants for polyethylene and polystyrene are established using linear polyethylene standards. After obtaining the constants, a conventional calibration method using two linear references for polyethylene molecular weight and polyethylene intrinsic viscosity as a function of elution volume is constructed using the two values, as shown in equations (9) and (10).
[0034]
number
[0035] The gpcBR branching index is a robust method for characterizing long-chain branching, as described in Yau, Wallace W., "Examples of Using 3D-GPC-TREF for Polyolefin Characterization," Macromol.Symp., 2007, 257, 29-45. This index prioritizes the entire polymer detector area, avoiding the conventional "per-slice" 3D-GPC calculations used in determining g' values and calculating branching frequencies. From TD-GPC data, the peak area method is used to determine the absolute weight-average molecular weight (MW) of the sample bulk as measured by a light scattering (LS) detector. (Abs) This method allows us to obtain the "per slice" ratio of the light scattering detector signal to the concentration detector signal, which is required in conventional g' determination.
[0036] Using TD-GPC, the intrinsic viscosity of the sample is also obtained independently using equation (11). The area calculation in equation (11) provides higher accuracy because, as the overall sample area, it is less affected by the variations caused by detector noise and TD-GPC settings to the baseline and integration limit. More importantly, the peak area calculation is unaffected by the detector volume offset. Similarly, the high-precision sample intrinsic viscosity ([h]) is obtained by the area method shown in equation (11).
[0037]
number
[0038] To determine the gpcBR branching index, the light scattering elution area of the sample polymer is used to determine the molecular weight (MW) of the sample. (Abs) Determine the intrinsic viscosity ([h]) of the sample polymer. Determine the intrinsic viscosity ([h]) of the sample using the elution area of the viscosity detector for the sample polymer.
[0039] First, the molecular weight and intrinsic viscosity of a linear polyethylene standard sample, such as SRM1475a or its equivalent, are determined using conventional calibration ("conventional calibration, cc") as functions of elution volume, according to equations (3) and (12).
[0040]
number
[0041] The GPCBR branch index is determined using equation (13).
[0042]
number
[0043] All statistical values with the subscript "cc" represent the respective elution volume, the corresponding conventional calibration method described above, and the concentration (c i Determined using "MW (Abs) The values for '' and ''[h] are measurements based on the mass detector, LALLS, and viscometer area. PEThe value of is adjusted iteratively until the linear reference sample has a gpcBR measurement of zero. For example, the final values of α and Log K for determining the gpcBR in this particular case are 0.725 and -3.391 for polyethylene and 0.722 and -3.993 for polystyrene, respectively. These polyethylene coefficients were then entered into Equation 13.
[0044] After determining the K and α values using the previously discussed procedure, the procedure is repeated using the branched sample. The branched sample is analyzed using the final Mark-Houwink constant obtained from the linear reference when the best "cc" calibration value is applied.
[0045] Differential Scanning Calorimetry (DSC). In preparation for a Differential Scanning Calorimetry (DSC) test, first, the pellet sample is loaded into a 1-inch diameter, 0.13 mm thick chase and compressed into a film at 190°C for approximately 10 seconds under a pressure of 25,000 lbs. The resulting film is then cooled to room temperature. Next, the film is subjected to a punch press to produce discs that fit into an aluminum DSC test pan. The discs are then individually weighed (note: sample weight is approximately 5-6 mg), placed in an aluminum pan, sealed, and inserted into the DSC test chamber.
[0046] In accordance with ASTM standard D3418, the DSC test is performed using a heating-cooling-heating cycle. First, the sample is heated to 150°C at a rate of 10°C / min and held isothermally for 5 minutes to remove thermal and process history. Next, the sample is rapidly cooled to -40°C at a rate of 10°C / min and held isothermally again for 5 minutes. Finally, for the second heating cycle, the sample is heated to 150°C at a rate of 10°C / min. For data analysis, the melting temperature and enthalpy of melting are taken from the second heating curve, while the enthalpy of crystallization is determined from the cooling curve. Enthalpy of melting (H fThe enthalpy of fusion and crystallization are obtained by integrating the DSC thermogram from -20°C to the end of melting and crystallization, respectively. Assuming the heat of fusion of 100% crystalline polyethylene is 292 J / g, the degree of crystallinity in wt% is calculated using the following equation A. DSC testing is performed using TA Instruments Discovery DSC, and data analysis is performed using TA Instruments Universal Analysis and the TRIOS software package. Equation A: Crystallinity %=((H f ) / 292J / g)×100
[0047] n-hexane extractables. As used herein, the term “hexane extractables” refers to the amount of n-hexane-soluble material extracted from the resulting polymer composition by n-hexane. The extraction process follows both the Food and Drug Administration (FDA) procedure (21 CFR 177.1520(d)(3)(ii)) and ASTM D5227 for determining the solvent extractable portion of polyolefins. The polymer pellets are compressed or extruded into a film having a thickness of 3-4 mils, and then cut into 1 x 1 inch square pieces. The film pieces are weighed (2.5 ± 0.05 g), then placed in a basket, and extracted in an n-hexane container at 49.5 ± 0.5 °C in a heated water bath for 2 hours, as described in ASTM D5227. After 2 hours, the film is removed, rinsed with clean n-hexane, and dried in a vacuum oven (80 ± 5 °C) under total vacuum for 2 hours. The film is then placed in a desiccator and allowed to cool to room temperature for at least 1 hour. Next, the film is reweighed, and the mass loss due to extraction in n-hexane is calculated. The n-hexane extractable material is reported in weight percent.
[0048] 1 1H NMR. Nuclear magnetic resonance (related to unsaturation). 1 (H NMR). For NMR spectroscopy to determine polyethylene unsaturation, see, e.g., Busico, V., et al., Macromolecules, 2005, 38, 6988.
[0049] 1 H NMR sample preparation. The sample was prepared by adding approximately 0.1 g of the sample to 3.25 g of 1,1,2,2-tetrachloroethane-d2 / perchloroethylene (TCE / PCE) in a 50 / 50 weight ratio, containing 0.001 M Cr(AcAc)3 and approximately 75 ppm butylated hydroxytoluene (BHT), in a Norell 1001-7 10 mm NMR tube. The sample was capped, sealed with Teflon tape, and then heated and vortexed at approximately 110-115°C to dissolve and ensure homogeneity.
[0050] 1 1H NMR data acquisition parameters. Using a Bruker AVANCE 600MHz spectrometer equipped with a Bruker high-temperature CryoProbe, at a sample temperature of 120°C. 1 1H NMR was performed. Spectra were acquired with a ZG pulse, 1.8-second AQ, 64 or 128 scans, and a 14-second relaxation delay.
[0051] 1 1H NMR data analysis. Unsaturated groups per 1000 carbon atoms (1000C) 1 1H NMR calculation. The spectrum was referenced to the residual proton signal of TCE at 6.0 ppm. The integral value of the entire polymer from approximately -0.5 to 2.5 ppm was set to an arbitrary value, e.g., 2000. The corresponding integral values for unsaturated groups were obtained (cis- and trans-vinylenes at approximately 5.40-5.60 ppm, trisubstituted compounds at approximately 5.16-5.35 ppm, vinyl at approximately 5.0-5.15 ppm, and vinylidene at approximately 4.75-4.85 ppm). The BHT-OH signal at approximately 4.9 ppm was not included in the integration region. Dividing the integral value of the entire polymer by 2 yields the total polymer carbon, 1000 in this example. The unsaturated group integral value, divided by the corresponding number of protons contributing to that integral value, represents the number of moles of each type of unsaturated group per 1000 moles of total polymer carbon. This is referred to as the number of unsaturated groups per 1000 carbon atoms ("100 / C").
[0052] 13 C nuclear magnetic resonance (branching) 13 (C NMR). 13 Samples for 13C NMR were prepared in a 10mm NMR tube by adding approximately 3g of 1,1,2,2-tetrachloroethane (TCE) containing 25 wt% TCE-d2 and 0.025M Cr(AcAc)3 to approximately 0.25g of polymer sample. The sample was then dissolved and homogenized by heating the tube and its contents to 120-140°C using a heating block and vortex mixer. Each dissolved sample was visually inspected to ensure homogeneity. The sample was thoroughly mixed immediately before analysis and kept from cooling until it was inserted into a heated NMR sample holder.
[0053] All data were acquired using a Bruker 600MHz spectrometer equipped with a 10mm high-temperature cryoprobe. At a sample temperature of 120°C, with a pulse repetition delay of 7.8 seconds, a flip angle of 90 degrees, and decoupling with reverse gate, the analysis was performed. 13 C data was acquired. All measurements were performed on a non-rotating sample in lock mode. The sample was thermally equilibrated before data acquisition. 13 The 30¹³C NMR chemical shift was internally referenced to a 30.0 ppm EEE triad. Table A lists the peak identifications used for branching measurements in LDPE. 6+ The value is C in LDPE. 6+ This is a direct measure of branching, and long branches are not distinguished from "chain ends". The peak at "32.2 ppm" represents the third carbon from the end of all chains or branches with 6 or more carbons, and is used for "C 6+ Determine the value.
[0054] [Table 1] CTA = Chain Translocation Agent or Terogen
[0055] Melt strength. Melt strength measurements were performed using Goettfert Rheotens 71.97 (Goettfert Inc.; Rock Hill, SC) coupled to a Goettfert Rheotester 2000 capillary rheometer. A molten sample (approximately 25-30 grams) was fed into a Goettfert Rheotester 2000 capillary rheometer with a length of 30 mm, a diameter of 2.0 mm, and a flat inlet angle (180 degrees) with an aspect ratio (length / diameter) of 15. After equilibrating the sample at 190°C for 10 minutes, the piston was operated at a constant piston speed of 0.265 mm / second. The standard test temperature was 190°C. The sample was then subjected to a set of accelerating nips located 100 mm below the die at a speed of 2.4 mm / second. 2 Uniaxial stretching was performed at the specified acceleration. Tensile force was recorded as a function of the nip roll winding speed. Melt strength was reported as the average plateau force (cN) before the strand fractured. The following conditions were used for melt strength measurement: plunger speed = 0.265 mm / sec, wheel acceleration = 2.4 mm / sec. 2 Capillary diameter = 2.0 mm, capillary length = 30 mm, and barrel diameter = 12 mm.
[0056] Viscosity. For preparation, the test sample was first placed in a 3.10 mm thick, 1.5 inch diameter chase and compressed using a Carver Hydraulic Press (model #4095.4NE2003) at a pressure of 25,000 lbs for 6.5 minutes at 190°C. After cooling to room temperature, the sample was removed and awaited rheological testing.
[0057] Frequency sweeps for DMS (Dynamic Mechanical Spectroscopy) were performed using 25 mm parallel plates at frequencies ranging from 0.1 to 100 rad / second. The test gap separating the plates was 1.8 mm, and a strain satisfying linear viscoelastic conditions, typically 10%, was used. Each test was performed under nitrogen atmosphere and isothermal conditions at 190°C. To begin the DMS test, the rheometer oven was first equilibrated at 190°C for at least 30 minutes, after which the sample was loaded into the test shape. The sample was then equilibrated in the closed oven for 1 minute. Next, the test gap was set to 1.8 mm, and the sample was allocated 5 minutes to allow the resulting normal force to relax. The oven was then quickly opened, and the sample was trimmed so that the polymer did not extend beyond the diameter of the plates. The oven was then closed again, and the DMS measurement was started. During the test, the shear modulus or storage modulus (G'), viscosity coefficient (G"), and complex viscosity are measured. All DMS frequency tests are performed using a TA Instruments ARES-G2 rotational rheometer. Data analysis is performed using TA Instruments TRIOS software. [Brief explanation of the drawing]
[0058] [Figure 1] This chart shows the chemical structures of different types of carbon-carbon double (unsaturated in polymer chains) bonds in vinylene, trisubstituted, vinyl, and vinylidene. [Figure 2] This is a block diagram of a process reaction system used to generate an example of the invention. [Figure 3] This is a perspective view of a mold-filled ("BFS") ampoule according to one embodiment of the present disclosure. [Modes for carrying out the invention]
[0059] This disclosure provides compositions. In one embodiment, the composition comprises an ethylene homopolymer having (i) a density of 0.9285 g / cc to 0.9315 g / cc, (ii) a melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) a hexane extractable content of 0.2% to 0.7% by weight.
[0060] 1. Composition The ethylene homopolymer composition of the present invention is produced under polymerization conditions in a polymerization reactor having an autoclave reactor portion and a tubular reactor portion (interchangeably referred to as an "autoclave / tubular hybrid"). The autoclave reactor portion has two or more injection points for the initiator and the ethylene monomer feed. The tubular portion has two or more injection points for the initiator and the ethylene monomer feed.
[0061] As used herein, the term “polymerization conditions” refers to process parameters in which ethylene is polymerized in the presence of a chain transfer agent. Polymerization conditions include, for example, those that affect polymerization reactor conditions (reactor type), reactor pressure, reactor temperature, reagent and polymer concentrations, solvent, carrier, residence time and distribution, molecular weight distribution and polymer structure. As used herein, the term polymerization conditions include (i) the presence of a chain transfer agent, which is a propionaldehyde, and (ii) the presence of a free radical initiator accompanied by an ethylene monomer in the polymerization reactor.
[0062] As used herein, “chain transfer agent” or CTA refers to a compound that can exchange an alkyl group or polymeryl group in the chain transfer agent with a growing polymer chain in the catalyst, resulting in the cessation of polymer chain growth under polymerization conditions. The chain transfer agent may be an aldehyde (e.g., propionaldehyde) and / or a ketone (e.g., methyl ethyl ketone), and other chain transfer agents that reduce the crystallinity of the resulting ethylene homopolymer, such as alpha-olefins or alkanes, e.g., propylene, isobutane, 1-butene, and n-butane, are excluded.
[0063] The “free radical initiator” (or “initiator”) as used herein may include organic initiators, such as dicumyl peroxide, di-tert-butyl peroxide, t-butyl perbenzoate, benzoyl peroxide, cumene hydroperoxide, t-butyl peroctoate, methyl ethyl ketone peroxide, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, lauryl peroxide, tert-butyl peracetate, and combinations thereof. Ethylene monomers are polymerized under polymerization conditions (polymerization reaction with propionaldehyde and one or more free radical initiators) to form ethylene homopolymers.
[0064] In one embodiment, the ethylene homopolymer is produced in an autoclave / tubular hybrid polymerization reactor under one, some, or all of the following polymerization conditions: (i) A first autoclave zone (upper reactor zone) operating at a temperature of 150°C to 170°C, or 160°C to 170°C, or 165°C to 170°C, and / or (ii) A second autoclave zone (bottom reactor zone) operating at a temperature of 150°C to 170°C, or 160°C to 170°C, or 165°C to 170°C, and / or (iii) A reactor inlet having a pressure of 2350 bar to 2500 bar, or 2400 bar to 2500 bar, or 2400 bar to 2450 bar, and / or (iv) A first tubular zone operating at a temperature peak of 230°C to 260°C, or 240°C to 260°C, or 250°C to 260°C, and / or (vi) A second tubular zone that operates at a temperature peak of 230°C to 260°C, or 240°C to 260°C, or 250°C to 260°C.
[0065] Under polymerization conditions, ethylene homopolymers produced in an autoclave / tubular hybrid polymerization reactor are LDPEs. Ethylene homopolymers possess one, some, or all of the following properties: (i) Densities of 0.9250 g / cc to 0.9350 g / cc, or 0.9290 g / cc to 0.9320 g / cc, or 0.9285 g / cc to 0.9315 g / cc, and / or (ii) Melt indices of 0.10 g / 10 min to 0.50 g / 10 min, or 0.20 g / 10 min to 0.49 g / 10 min, or 0.32 g / 10 min to 0.48 g / 10 min, and / or (iii) Hexane extractable content of 0.1% to 0.8% by weight, or 0.2% to 0.7% by weight, or 0.3% to 0.6% by weight, or 0.3% to 0.5% by weight.
[0066] In one embodiment, the ethylene homopolymer produced in an autoclave / tubular hybrid under polymerization conditions is LDPE. The ethylene homopolymer has one, some, or all of the following properties: (i) Densities of 0.9250 g / cc to 0.9350 g / cc, or 0.9290 g / cc to 0.9320 g / cc, or 0.9285 g / cc to 0.9315 g / cc, and / or (ii) Melt indices of 0.10 g / 10 min to 0.50 g / 10 min, or 0.20 g / 10 min to 0.49 g / 10 min, or 0.32 g / 10 min to 0.48 g / 10 min, and / or (iii) Hexane extractable content of 0.1% to 0.8% by weight, or 0.2% to 0.7% by weight, or 0.3% to 0.6% by weight, or 0.3% to 0.5% by weight, and / or (iv) A degree of crystallinity of 54% to 62%, or 54% to 58%, or 55% to 58%, or 56% to 57%, and / or (v) Absolute weight-average molecular weight (Mw) of 150,000 to 220,000 g / mol, or 170,000 to 210,000 g / mol, or 190,000 to 210,000 g / mol (Abs) ), and / or (vi) Mw(cc) / Mn(cc) of 4.5-6.5 or 5.0-5.5, and / or (vii) gpcBR versions 1.2~2.0, or 1.4~1.9, or 1.5~1.8, and / or (viii) vinylidene content of 0.050 / 1000 carbon to 0.080 / 1000 carbon or 0.060 / 1000 carbon to 0.070 / 1000 carbon, and / or (ix) Total unsaturation per 1000 carbon atoms of 0.12-0.15 or 0.12-0.14.
[0067] 2.Goods This disclosure provides articles. In one embodiment, the article comprises an ethylene homopolymer of the present invention. The ethylene homopolymer has (i) a density of 0.9285 g / cc to 0.9315 g / cc, (ii) a melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) a hexane extractable content of 0.2% to 0.7% by weight.
[0068] In one embodiment, the article is a container. The container includes side walls. The side walls are made of an ethylene homopolymer.
[0069] In one embodiment, the container is a BFS container (a "BFS" container). As used herein, a "BFS container" is a container manufactured in an automated manufacturing process by which polymer containers, such as bottles or ampoules, are blow-molded, filled, and sealed in a continuous operation. BFS containers are manufactured in a sterile, sealed area inside a machine. The advantage of the BFS manufacturing process is that the process is a closed, automated system. BFS containers are formed and filled with a sterile solution within a BFS machine, and the BFS containers are sealed with limited or no human intervention.
[0070] Figure 3 shows a BFS container 110. In the BFS container manufacturing process, the composition of the present invention (i.e., LDPE and an optional additive) is melted and extruded into a side wall 112 ("parison" or continuous side wall) formed into the shape of a cylindrical tube, and sterile air or nitrogen is blown into the cylindrical tube to form the composition of the present invention (in its molten state) into the shape of the mold, thereby forming the container. Cooling of the container begins within seconds after it is formed, as the mold cools. Next, the drug 114 (typically liquid, semi-liquid, or gel) is filled into the newly formed polymer container while it is still inside the mold. The BFS machine then closes the side wall 112 on itself by sealing the upper and lower ends of the cylindrical tube, thereby forming a sealed BFS container 110 having a body portion 116, a top 118, a bottom 120, and a side wall 112 defining a closed chamber 122 containing the drug 114 (or cosmetic). In other words, the BFS container 110 is constructed from a single continuous side wall 112. The BFS container also includes a tab 124 (also constructed from the composition of the present invention) for opening the container 110 to dispense or otherwise release the drug 114 from the chamber 122.
[0071] The side walls 112 of the container 110 are made of the ethylene homopolymer of the present invention. The ethylene homopolymer has one, some, or all of the following properties: (i) Densities of 0.9250 g / cc to 0.9350 g / cc, or 0.9290 g / cc to 0.9320 g / cc, or 0.9285 g / cc to 0.9315 g / cc, and / or (ii) Melt indices of 0.10 g / 10 min to 0.50 g / 10 min, or 0.20 g / 10 min to 0.49 g / 10 min, or 0.32 g / 10 min to 0.48 g / 10 min, and / or (iii) Hexane extractable content of 0.1% to 0.8% by weight, or 0.2% to 0.7% by weight, or 0.3% to 0.6% by weight, or 0.3% to 0.5% by weight.
[0072] In one embodiment, the side wall 112 of the container 110 is made of the ethylene homopolymer of the present invention. The ethylene homopolymer has one, some, or all of the following properties: (i) Densities of 0.9250 g / cc to 0.9350 g / cc, or 0.9290 g / cc to 0.9320 g / cc, or 0.9285 g / cc to 0.9315 g / cc, and / or (ii) Melt indices of 0.10 g / 10 min to 0.50 g / 10 min, or 0.20 g / 10 min to 0.49 g / 10 min, or 0.32 g / 10 min to 0.48 g / 10 min, and / or (iii) Hexane extractable content of 0.1% to 0.8% by weight, or 0.2% to 0.7% by weight, or 0.3% to 0.6% by weight, or 0.3% to 0.5% by weight, and / or (iv) A degree of crystallinity of 54% to 62%, or 54% to 62%, or 54% to 58%, or 55% to 58%, or 56% to 57%, and / or (v) Absolute weight-average molecular weight (Mw) of 150,000 to 220,000 g / mol, or 170,000 to 210,000 g / mol, or 190,000 to 210,000 g / mol (Abs) ), and / or (vi) Mw(cc) / Mn(cc) of 4.5-6.5 or 5.0-5.5, and / or (vii) gpcBR versions 1.2~2.0, or 1.4~1.9, or 1.5~1.8, and / or (viii) vinylidene content of 0.050 / 1000 carbon to 0.080 / 1000 carbon or 0.060 / 1000 carbon to 0.070 / 1000 carbon, and / or (ix) Total unsaturation per 1000 carbon atoms of 0.12-0.15 or 0.12-0.14.
[0073] Non-limiting examples of drugs present in the chamber 122 and in direct contact with the side wall 112 include liquid eye drops (such as sterile eye drops), inhaled anesthetics, biological agents, cleaning agents, and vaccines.
[0074] The side wall 112 may have a uniform thickness, or its thickness may vary along the length of the BFS container 110 from the top 118 to the body portion 116 and the bottom 120. In one embodiment, the continuous side wall 112 includes a closing top 118, a body portion 116, and a bottom 120. In a further embodiment, the continuous side wall 112 has a thickness of 0.3 mm to 2.5 mm, or 0.3 mm to 1.5 mm, or 0.3 mm to 1.0 mm, and forms a closed chamber having a volume of 0.1 cubic centimeters to 200 cc, or 0.5 cc to 100 cc, or 1.0 cc to 50 cc.
[0075] In one embodiment, the side wall 112 is a continuous side wall that is seamless and / or unsealed and / or unheat-sealed.
[0076] In one embodiment, the main body portion 116 is a continuous main body portion, has no seams, and / or the main body portion 116 does not have heat fusion.
[0077] Without limiting ourselves to any particular example, several embodiments of this disclosure will be described in detail in the following examples. [Examples]
[0078] The ethylene homopolymer of the present invention was produced via a high-pressure free-radical initiated polymerization process in an autoclave / tubular hybrid polymerization reactor, as shown in Figure 2. Autoclave / tubular hybrid polymerization reactor A comprises an autoclave reactor section 12 (or "AC reactor") and a tubular reactor section 13 (or "two-zone reactor"). The autoclave reactor section 12 has two or more injection points for initiators and monomer feeds. The tubular reactor section 13 has two peroxide injection points, thereby becoming a two-zone tubular reactor 13 in series with the autoclave reactor 12.
[0079] Autoclave / tubular hybrid polymerization reactor A includes an autoclave reactor section 12 and a tubular reactor section 13. Autoclave / tubular hybrid polymerization reactor A is a component of process reaction system 19. Process reaction system 19 in Figure 2 is a partially closed-loop, double-recirculation, high-pressure, low-density polyethylene production system. Process reaction system 19 includes a fresh ethylene feed 1, a booster compressor 14, a primary compressor 15, and a hyper-compressor 16, and autoclave / tubular hybrid polymerization reactor A includes an autoclave reactor section 12 and a tubular reactor section 13. Autoclave / tubular hybrid polymerization reactor includes an autoclave reactor section 12 and a tubular reactor section 13. Autoclave reactor section 12 includes an autoclave reactor section having three (or four) adiabatic autoclave reactor zones connected to a tubular reactor section having a two-zone tubular reactor 13. The autoclave reactor section 12 contains ethylene feed 11 and ethylene feed 3, divided 50 / 50. The first ethylene feed 11 is supplied to the top of the autoclave reactor section 12 (i.e., autoclave zone 1), and the second ethylene feed 3 is supplied to the side of the autoclave reactor section 12 in autoclave zone 2. A peroxide initiator is injected into the autoclave reactor section to initiate the polymerization reaction. The peroxide initiator is also injected into the tubular reactor section 13. The tubular reactor section 13 uses a cooling jacket fitted around the outer shell of the tubular reactor. The polymer product (ethylene homopolymer) and ethylene monomers were separated using a high-pressure separator 17, high-pressure recirculation, a low-pressure separator 18, and low-pressure recirculation. A chain transfer agent (CTA) was then injected into the suction side of the hypercompressor 16.
[0080] The polymerization conditions used to produce the ethylene homopolymer and comparative samples of the present invention are shown in Tables 1A, 1B, 1C, and 1D below. The numbers in parentheses in the "Characteristics" column of Tables 1A and 1C correspond to the reference numbers in Figure 2.
[0081] [Table 2]
[0082] The free radical initiator injected into the autoclave reactor section is tert-butylperoxypivalate. The free radical initiator for the tubular reactor section is a mixture of tert-butylperoxy-2-ethylhexanoate and tert-butylperoxyacetate. Table 1B below provides the range of peroxide concentrations used.
[0083] [Table 3]
[0084] [Table 4] * CJ (cooling jacket) = cooling jacket
[0085] The applicant found that using propionaldehyde ("PA") (Table 1C) as the sole CTA contributes to (i) narrowing the Mw / Mn of the ethylene homopolymer, (ii) increasing the melt strength by having a carbonyl form that causes more long-chain branching (LCB) by forming weak bonds with hydrogen, and (iii) increasing the degree of crystallinity due to the high reactivity of propionaldehyde.
[0086] Connect the cooling jackets ("CJ") shown in Table 1C to different cooling drums operating at different pressures. The pressure in the cooling drums can vary between 6 and 12 bar.
[0087] Table 1D below provides the polymerization conditions for comparative samples ("CS") CS1 to CS5. In the table, "tube" refers to a tubular polymerization reactor, and "AC-LT" refers to the autoclave / tubular hybrid polymerization reactor shown in Figure 2.
[0088] [Table 5]
[0089] Examples 1-3 (IE1-3) of the present invention were produced using the polymerization conditions listed in Tables 1A, 1B, and 1C. The characteristics of the inventive examples ("IE") IE1-3 and comparative samples 1-5 (CS1-5) are shown in Table 2 below.
[0090] [Table 6]
[0091] The branch values for CS1-5 and IE2 are provided in Table 3 below.
[0092] Table 3: 13 Branching values for CS1-5 and IE2 measured by 13C NMR (during branching per 1000 carbon atoms).
[0093] [Table 7]
[0094] The unsaturated values for CS1-5 and IE2 are provided in Table 4 below.
[0095] Table 4: 1 Unsaturation values of CS1-5 and IE2 (per 1000 carbon atoms) measured by 1H NMR.
[0096] [Table 8]
[0097] Table 5: Molecular weight values of IE1-3 and CS1-5
[0098] [Table 9]
[0099] [Table 10]
[0100] [Table 11]
[0101] Although not bound by any particular theory, the applicant has considered the polymerization conditions in Tables 1A, 1B, and 1C, as well as (i) Autoclave Zone 1 temperature of 168℃, (ii) Autoclave zone 2 temperature of 166.8℃, (iii) Peak temperature of tubular zone 1 at 257°C, (iv) 256°C tubular zone 2 peak temperature, (v) Reactor pressure of 2440 barg, and (vi) By polymerizing ethylene monomer in an autoclave / tubular hybrid polymerization reactor under polymerization conditions including a propionaldehyde supply rate of 16.7 kg / hour, Unexpectedly, we discovered that ethylene homopolymers with high purity (less than 0.8% by weight of hexane extractable material) can be obtained, with a density of 0.9285 to 0.9315 g / cc, high crystallinity (over 50%), and low MI (less than 0.5 g / 10 min MI). This is desirable for in-mold filling applications, particularly in-mold filling medical applications.
[0102] Each of IE1-3 has a lower hexane extractable content (i.e., higher purity) compared to CS1-5 (0.63-2.02% for CS1-5, compared to IE1-3-0.38-0.41%), and exhibits a high degree of crystallinity (56.2-56.8%) and a low MI (0.40-0.43 g / 10 min), which are desirable for medical molding and filling applications.
[0103] This disclosure is not limited to the embodiments and examples contained herein, and is specifically intended to include modified forms of embodiments, including parts of embodiments and combinations of elements of different embodiments, to the extent that they fall within the scope of the following claims.
Claims
1. A composition, It is an ethylene homopolymer, (i) Density of 0.9285 g / cc to 0.9315 g / cc, (ii) Melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) A composition comprising an ethylene homopolymer having a hexane extractable content of 0.2% to 0.7% by weight.
2. The ethylene homopolymer, (iv) The composition according to claim 1, having a degree of crystallinity of 54% to 58%.
3. The ethylene homopolymer, (v) Absolute weight-average molecular weight (Mw) of 150,000 g / mol to 220,000 g / mol (Abs) The composition according to claim 1 or 2, having )
4. The ethylene homopolymer, (vi) The composition according to any one of claims 1 to 3, having Mw(cc) / Mn(cc) of 4.5 to 6.
5.
5. Articles, It is an ethylene homopolymer, (i) Density of 0.9285 g / cc to 0.9315 g / cc, (ii) Melt index of 0.32 g / 10 min to 0.48 g / 10 min, and (iii) An article comprising an ethylene homopolymer having a hexane extractable content of 0.2% to 0.7% by weight.
6. The ethylene homopolymer, (iv) The article according to claim 5, having a degree of crystallinity of 54% to 58%.
7. The ethylene homopolymer, (v) Absolute weight-average molecular weight (Mw) of 150,000 g / mol to 220,000 g / mol (Abs) The article according to claim 5 or 6, having )
8. The article according to any one of claims 5 to 7, wherein the ethylene homopolymer has a ratio of 4.5 to 6.5 Mw(cc) / Mn(cc).
9. The aforementioned article, The article according to any one of claims 5 to 8, which is a container having a side wall containing the ethylene homopolymer.
10. The aforementioned side wall defines the closed chamber, The article according to claim 9, wherein the drug is present in the closed chamber.
11. The article according to claim 9 or 10, wherein the side wall has a single-layer structure and a thickness of 0.3 mm to 2.5 mm.
12. The article according to any one of claims 9 to 11, wherein the closed chamber has a volume of 0.1 cc to 200 cc.
13. The article according to any one of claims 9 to 12, wherein the container is a mold-and-fill container.